Effect of Sulfur Sources on Megathyrsus Maximus 'Mombaca' Grass Cultivated in a Typic Ultisol - Santos, Luiz Felipe de Melo [UNESP]; Lapaz, Allan Marcos [UNESP]; Ribeiro, Filipe Virgilio [UNESP]; Virgilio, Igor Ribeiro [UNESP]; Meirelles, Guilherme Constantino [UNESP]; Lira, Maikon Vinicius da Silva [UNESP]; Soares Filho, Cecilio Viega [UNESP]; Bonini, Carolina Santos Batista [UNESP]; Reis, Andre Rodrigues dos [UNESP]; Moreira, Adonis; Heinrichs, Reges [UNESP] (Taylor & Francis Inc, 2020)
The deficiency of sulfur (S) in agricultural soils has been aggravated in recent decades, mainly by the application of high concentration fertilizers that are S-free and intensive agricultural activities. This study evaluated forage yield, nutritional status and inorganic sulfate-S in soil when submitted to levels and sources of sulfur, including elemental sulfur, of the 'Mombaca' grass in a Typic Ultisol. The experimental design was completely randomized arrangement in a 5 x 4 factorial design, with five S rates (0, 50, 100, 150, and 200 mg kg(-1)) and four S sources. The sources were elemental sulfur pastilles (ESPA), phosphogypsum (GY), gypsite (GI), and elemental sulfur powder (ESPO). The results showed that the S-use efficiency with the GI, GY and ESPO sources was obtained with the supply of 50 mg kg(-1) of S, and was enough to optimize the 'Mombaca' grass yield and promote a better quality for the nutritional status of the forage. The ESPA source had an S leaf concentration below the adequate range and resulted in lower yield values in relation to the other S sources evaluated. The SPAD index in the newly expanded leaves was shown to be an indicator of shoot dry weight (SDW) yield and could be used as a pre-diagnosis of the S-efficiency in 'Mombaca' grass. The soil processes associated to the availability of S had a great influence on the granulometry, which drove the SDW yield and S use efficiency with the source ESPO in relation to ESPA.
Keywords: Fertilizer application; soil fertility; sulfate; pasture; Megathyrsus maximus